Exploring the Role of Student Activity Units in Exploring the Potential and Achievements of Students of the Social Sciences Education Department of UIN Syarif Hidayatullah Jakarta - Rekhael Ramadhanish; Afina Kamila; Yurni latifah; Dwi Diah Fadilah; Arif Saefudin (EDUTECH, 2026)
This study explores the role of Student Activity Units (UKM) in developing the potential and improving the achievements of students in the Social Studies Education Department at Syarif Hidayatullah State Islamic University Jakarta. Using a qualitative case study approach, data were obtained through interviews, observations, and documentation involving students active in the LDK Syahid and FORSA UKM. The findings show that participation in UKM helps students sharpen their leadership, communication, and discipline skills, as well as enhance both academic and non-academic achievements. UKM also contributes to shaping student character to become more independent, responsible, and hardworking. Despite challenges such as uneven internal coordination, the support of campus facilities and a familial atmosphere help sustain the activities of UKM. This study affirms that UKM serves as an essential partner for the university in supporting comprehensive and character-based student development.